2018
DOI: 10.30831/akukeg.358211
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Bilgiler Öğretiminde Müze ve Tarihi Mekân Kullanımının 7. Sınıf Öğrencilerinin Sosyal Bilgiler Algılarına Etkisi: Bir Eylem Araştırması

Abstract: The aim of this study is twofold. The first one is to practice the teaching activities designed to make use of museums and historical places within the context of grade seven social studies course. The second one is to reveal how and in which ways these activities influence students' perceptions of social studies. Designed as an action research, the current study employs 36 grade seven students (20 girls and 16 boys) attending to a public secondary school located in the district of Yunusemre attached to Manisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…Araştırma sonucunda deney grubu öğrencilerinin bilişsel olarak olumlu etkilendikleri, alanyazında yapılan diğer araştırmalarla uyumludur (Aydoğan, 2020;Çetindağ-Kuşan, 2005;Çulha, 2006;Demirboğa, 2010;Filiz, 2010;Güler, 2011;Üztemur, Dinç ve Acun, 2018b;Yazıcıoğlu, 2010;Yeşilbursa, 2006;Yıldırım, 2020;Yorulmaz, 2016). Araştırma bulgularına göre sosyal bilgiler öğretim programında yer alan "SB.5.2.2.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
See 1 more Smart Citation
“…Araştırma sonucunda deney grubu öğrencilerinin bilişsel olarak olumlu etkilendikleri, alanyazında yapılan diğer araştırmalarla uyumludur (Aydoğan, 2020;Çetindağ-Kuşan, 2005;Çulha, 2006;Demirboğa, 2010;Filiz, 2010;Güler, 2011;Üztemur, Dinç ve Acun, 2018b;Yazıcıoğlu, 2010;Yeşilbursa, 2006;Yıldırım, 2020;Yorulmaz, 2016). Araştırma bulgularına göre sosyal bilgiler öğretim programında yer alan "SB.5.2.2.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…Öğrencilerinin dokunarak, orijinal Müze Eğitimi Uygulamalarının Öğrencilerin Somut Kültürel Miras ve Sosyal… [1744] eseri görerek daha fazla duyuyu işe koştuğundan bilişsel açıdan fayda sağlayacaktır. Araştırma sonucunda deney grubu öğrencilerinin duyuşsal olarak olumlu etkilendikleri alanyazında yapılan diğer araştırmalarla uyumludur (Aktekin, 2009;Aydoğan, 2020;Çetindağ-Kuşan, 2005;Çulha, 2006;Danacı-Polat, 2019;Demirboğa, 2010;Filiz, 2010;Güler, 2011;Işık, 2008;Nişancı, 2010;Tunç-Şahin, 2011;Üztemur, Dinç, Acun, 2018b;Yazıcıoğlu, 2010;Yorulmaz, 2016;Zayimoğlu-Öztürk, 2014). Bu araştırma için seçilen müzelere özel olarak geliştirilen etkinliklerde en çok dikkat edilen unsur programdaki değer ve becerilerinden müzelerin içeriğine uygun olanlarını seçip öğrencilerde değer ve beceri geliştirmeye çalışmaktır.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…A review of the literature related to the topic reveals no direct studies on the use of memory places as an out-of-school learning environments in social studies. However, the existence of some studies has been identified regarding the use of memory places in teaching (Karatekin et al, 2017;Çapkın, 2018), in action research (Öztaşçı, 2017;Hayta & Akhan, 2014;Akça Berk, 2012), in utilizing historical places in social studies (Üztemur et al, 2018a;Üztemur, Dinç & Acun, 2018b), and in creative drama with action research (Bayram & Çalışkan, 2019;Aysal, 2012). Additionally, it is observed that research on memory places is generally concentrated in the fields of sociology and architecture (Ak, 2018;Aktin, 2017;Aydoğan, 2016;Biçel, 2013;Biricik, 2016;Bilginer Erdoğan, 2013;Cihangiroğlu, 2016;Cihangiroğlu, 2019;Doğu & Varkal Deligöz, 2017;Dural Tasouji, 2013;Ekman, 2009;Karakaş, 2019;Kır, 2016;Kırcı, 2015;Mowla, 2004;Öymen Özak & Pulat Gökmen, 2009;Parmaksız, 2012;Pösteki, 2012;Saç, 2009;Sarıkaya Levent, 2017;Suda, 2017;Tekin, 2017;Uzunoğlu, 2018;Yıldırım, 2018;Yüksel, 2019).…”
Section: Introductionmentioning
confidence: 99%